An Experimental Study on the Smart Home Concept with PV and Energy Management and Control Strategy Using an Open Source Platform. Issue 1 (1st January 2019) - Ghouari, Adel; Hamouda, Chaâbane; Chaghi, Abdelaziz; Chahdi, Mohamed
ABSTRACT: The smart grid system is key to the new electrical network infrastructure. It takes into account the use of the new information and communication technologies (ITC) and the integration of the renewable energy power generation (photovoltaics PV, concentrated solar power CSP, wind, etc). The smart grid promises better management and control of energy sources. The application of the smart grid, especially, in Algeria allows the optimal control of the electricity demand since the latter keeps rising continuously. The use of smart grid allows the rationalization of the electricity consumption in smart homes through appliance automated control. Input energy savings result in the reduction of c emission. Herein, we present a new energy management strategy tested in an experimental smart home (SM). The implemented management approach was made possible by using a new electronic system that allowed the control of all appliances via the internet network. For this purpose, a dynamic monitoring web interface was developed under an open source platform in order to process the whole data delivered by the system. The final output of the system which consists of a balance between all types of energy involved, including CO2 gas emission, is displayed. It is only then that the user can take adequate decision and establish the priorities for rational use of the energy available.